Devido processo legal na relação de emprego: contraditório e motivação - poder disciplinar e cessação do contrato de trabalho - Vale, Silvia Isabelle Ribeiro Teixeira do (2018)
The main objective of this study is to analyze the principle of due process in its greatest potentiality, investigating how and to what extent this ancestral clause has effectiveness in the employment relationship, limiting the disciplinary labor power, by imposing a procedure for fair dismissals motive, in honor of the principles of the adversary and the ample defense. The Federal Constitution of 1988 is expressed by prohibiting arbitrary dismissal, considering it an unlawful act. However, in addition to the aforementioned protection, the principle of due process requires the employer to motivate the act of resignation, be it individual or collective, hence the new rule brought by Article 477-A of the Consolidation of Labor Laws is unconstitutional